Exploration of epidemiologic profile and strategic prevention framework for surgical site infection rates in a tertiary care hospital of Bhopal city - Goyal, Vidit; Kaushal, Rituja (International Journal Of Community Medicine And Public Health, 2018)
Background: Post-operative surgical site infections are deadlock for any successful surgery. This exigency triggers draining of extra resources for management of the quagmire. Methods: This prospective direct surveillance study based on incidence design was undertaken to gauge and estimate the nature of propensity of various surgical site infections in a tertiary care hospital over a period of twelve months. Results: Calculated cumulative SSI rate for the year 2016 was found to be 4.32%. Conclusions: It was concluded that a multidisciplinary approach integrating periodic training sessions on infection control, checklists based routine surveillance & following some benchmark etc. are the linchpin in controlling hospital acquired infections including surgical site infection rates in any clinical setting.